Effectiveness of combined ar-rahman murottal therapy and lavender aromatherapy for family anxiety reduction in intensive care unit waiting rooms: A systematic review - Sukran Suyanto; Ahmad Ikhlasul Amal; Erna Melastuti; Indah Sri Wahyuningsih (Lentera Perawat, 2026)
Background: Family members who wait for patients in intensive care units frequently experience anxiety due to uncertainty, emotional burden, and fear related to critical illness. Non-pharmacological interventions such as Qur’anic murottal therapy and lavender aromatherapy have been increasingly explored because both approaches may promote relaxation, emotional comfort, and psychological stability in stressful clinical situations. However, evidence regarding their combined effectiveness for reducing anxiety among families in ICU waiting rooms remains limited and scattered across different clinical contexts. Objective: This systematic review aimed to examine the effectiveness of combined Ar-Rahman murottal therapy and lavender aromatherapy for reducing anxiety among family members in intensive care unit waiting rooms. Methods: This study used a systematic review design and followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guideline. Literature searches were conducted in ClinicalKey for Nursing, SAGE Journals, ProQuest, and Google Scholar using combinations of keywords related to murottal therapy, lavender aromatherapy, anxiety, ICU, and family health. Studies published in English or Indonesian within the last 10 years were considered. Experimental and quasi-experimental studies were included, while irrelevant studies, methodologically weak articles, grey literature, and studies outside the review focus were excluded. Study selection, quality appraisal, and data extraction were conducted independently by two reviewers. Of 1,942 records initially identified, 12 full-text articles were assessed, 2 were excluded because of high risk of bias, and 10 studies were included in the final synthesis. Results: The included studies showed that the combination of Ar-Rahman murottal therapy and lavender aromatherapy was associated with reduced anxiety across several clinical contexts. The strongest evidence came from studies involving family members in ICU waiting rooms, where the combined intervention significantly reduced anxiety levels. Indirect evidence from preoperative, inpatient, and waiting-room populations supported the anxiolytic potential of both therapies. Overall, the findings suggested a consistent positive direction of effect, although the evidence remained heterogeneous in terms of population, setting, intervention duration, and measurement instruments. Conclusion: Combined Ar-Rahman murottal therapy and lavender aromatherapy appears to be a promising complementary intervention for reducing anxiety among family members in ICU waiting rooms. Nevertheless, further rigorous studies focusing specifically on ICU family populations are needed to strengthen the evidence base and support wider implementation in family-centered critical care nursing.